Structural and non-structural ways of managing floods with respect to the climate change situation - Salleh, Md Noor; Hakim, Nur Wajihah; Al-Mamun, Abdullah; Ayob, Mohd Fairullazi; Sekaran, Thayalam; Ismail, Mohd Azmi; Mat Amin, Mohd Zaki; , (2020)
Paper presented at“Kolokium Kebangsaan Penyelidikan & Pembangunan Air 2020.